Identification of time of liquefaction triggering - Ozener, Pelin Tohumcu; Greenfield, Michael W.; Sideras, Samuel S.; Kramer, Steven L. (ELSEVIER SCI LTD, 2020)
The paper describes a procedure for estimating the time at which liquefaction has been triggered from ground motions recorded on or within liquefiable soils subjected to strong earthquake shaking. The procedure makes use of time-frequency analyses, implemented in the form of Stockwell spectrograms, to determine the likely point at which a layer of soil within the profile underlying a strong motion instrument has softened to a degree that indicates triggering of liquefaction. The procedure can be applied to sites with vertical arrays using Stockwell spectral ratios, and to sites with only surface motions using both the motions themselves and H/V Stockwell spectral ratios. To minimize the potential for false readings by surface wave arrivals, azimuthal variability of triggering time values is also considered. The paper also describes benefits of knowledge of triggering time ranging from identification of liquefaction based on ground motion characteristics to improved prediction of the effects of liquefaction on soil and soil-structure systems.
Keywords: Liquefaction; Triggering; Timing; Site response; Stockwell transform; SOIL LIQUEFACTION; EARTHQUAKE; FREQUENCY; VELOCITY; KOBE; CYCLES; NUMBER; ARRAY; CITY; Engineering; Geology